Characterization of Silk Fibroin/Chitosan 3D Porous Scaffold and In Vitro Cytology - Zeng, Shuguang; Liu, Lei; Shi, Yong; Qiu, Junqi; Fang, Wei; Rong, Mingdeng; Guo, Zehong; Gao, Wenfeng (PLOS ONE, 2015)
Bone tissue engineering is a powerful tool to treat bone defects caused by trauma, infection, tumors and other factors. Both silk fibroin (SF) and chitosan (CS) are non-toxic and have good biocompatibility, but are poor biological scaffolds when used alone. In this study, the microscopic structure and related properties of SF/CS composite scaffolds with different component ratios were examined. The scaffold material most suitable for osteoblast growth was determined, and these results offer an experimental basis for the future reconstruction of bone defects. First, via freeze-drying and chemical crosslinking methods, SF/CS composites with different component ratios were prepared and their structure was characterized. Changes in the internal structure of the SF and CS mixture were observed, confirming that the mutual modification between the two components was complete and stable. The internal structure of the composite material was porous and three-dimensional with a porosity above 90%. We next studied the pore size, swelling ratio, water absorption ratio, degradation and in vitro cell proliferation. For the 40% SF-60% CS group, the pore size of the scaffold was suitable for the growth of osteoblasts, and the rate of degradation was steady. This favors the early adhesion, growth and proliferation of MG-63 cells. In addition to good biocompatibility and satisfactory cell affinity, this material promotes the secretion of extracellular matrix materials by osteoblasts. Thus, 40% SF-60% CS is a good material for bone tissue engineering.